Docosahexaenoic acid supports feto‐placental growth and protects cardiovascular and cognitive function: A mini review. Issue 10 (8th March 2016) - Duttaroy, Asim K.
Abstract : Docosahexaenoic acid, 22:6n‐3 (DHA), one of the important members of the n‐3 fatty acids, positively affects overall human health. DHA is now regarded as an important dietary ingredient required throughout the life cycle including from early placentation, feto‐placental growth and development to the maintenance of general health. Although DHA can be synthesized in the body from its precursor, alpha linolenic acid, 18:3n‐3 (ALA), but the main effective dietary source of DHA is seafoods. The beneficial effects of DHA on human health are known for long time; only recently the mechanisms of action of DHA and its derivatives at both cellular and molecular levels are emerging. This mini review focuses on the roles of DHA and its metabolites on early placentation, feto‐placental growth and development, cardiovascular disease, immune and cognitive disorders. Practical applications: This review describes the importance of docosahexaenoic acid in human health. This mini review focuses on the roles of DHA on early placentation, feto‐placental growth and development, cardiovascular disease, immune and cognitive disorders. Docosahexaenoic acid affects feto‐placental growth and development, brain structure and function, cardiovascular and immune systems. DHA is now regarded as an important dietary ingredient required in early placentation, feto‐placental growth, and development to the maintenance of general health. DHA can be synthesized in the body from its precursor, alpha linolenic acid, 18:3n‐3 but the main effective dietary source of DHA is seafoods. An optimal intake of DHA is especially essential for pregnant mothers to ensure adequate feto‐placental growth and for fetal brain structure and function. DHA is essential for the adult brain, where it impacts the brain's structure and signaling systems. DHA modulates cardiovascular and immune systems via different structural and signaling mechanisms. Abstract : Docosahexaenoic acid affects feto‐placental growth and development, brain structure and function, cardiovascular and immune systems. DHA is now regarded as an important dietary ingredient required in early placentation, feto‐placental growth, and development to the maintenance of general health. DHA can be synthesized in the body from its precursor, alpha linolenic acid, 18:3n‐3 but the main effective dietary source of DHA is seafoods. An optimal intake of DHA is especially essential for pregnant mothers to ensure adequate feto‐placental growth and for fetal brain structure and function. DHA is essential for the adult brain, where it impacts the brain's structure and signaling systems. DHA modulates cardiovascular and immune systems via different structural and signaling mechanisms.